Mechanical properties comparison between new and recycled polyethylene terephthalate glycol obtained from fused deposition modelling waste. Issue 4 (24th May 2021) - Bergonzi, Lorenzo; Vettori, Matteo
Abstract: The recycling of materials and the efficient use of resources are nowadays fundamental in a circular economy perspective. This concept also applies to additive manufacturing (AM) where waste can be reused to produce new material. Using mostly thermoplastic polymers, fused deposition modeling (FDM) is an AM technique that allows to melt waste materials and, successively, using a suitable extruder, obtain new filament. In the process, polymers are subject to multiple re‐melting and polymer orientations by extrusion operations. The aim of this work is to evaluate the influence of the recycling process over polyethylene terephthalate glycol‐modified (PETG) mechanical properties by tensile testing of samples produced using pure and recycled material. Furthermore, filament itself has been tested to evaluate recycle process influence before FDM printing.